Bacteriological profile of blood stream infections among febrile patients attending a tertiary care centre of Western Nepal - Dharm Raj Bhatta (Asian Journal of Medical Sciences, 2013)
Background Blood stream infections (BSI) are significant cause of morbidity and mortality in the world. This study was conducted to determine the common bacterial agents associated with BSI with their antimicrobial susceptibility patterns in a tertiary care centre in the Western region of Nepal.